Understanding heritage language acquisition : some contributions from the research on heritage speakers of European Portuguese - Flores, Cristina (2015)
The present paper aims to contribute to our understanding of heritage language acquisition by focusing on the results of three studies on heritage speakers of European Portuguese living in Germany (Flores and Barbosa, 2014, Santos and Flores, 2013 and Rinke and Flores, 2014), thus highlighting the European perspective on this topic. The participants of these studies are second-generation immigrants who use their heritage language productively in their daily interactions. In particular it is argued that heritage speakers are highly proficient bilingual speakers who develop a particular linguistic knowledge because they are exposed to particular input conditions. In this sense, the proficiency of heritage speakers cannot be described as the outcome of a deficient, incomplete acquisition process, but rather as an instance of native language development.